Estimating infection-related human mobility networks based on time series data of COVID-19 infection in Japan - Yamada, Tetsuya; Shi, Shoi (Applied Sciences, 2022)
Comprehensive and evidence-based countermeasures against emerging infectious diseases have become increasingly important in recent years. COVID-19 and many other infectious diseases are spread by human movement and contact, but complex transportation networks in the 21st century make it difficult to predict disease spread in rapidly changing situations. It is especially challenging to estimate the network of infection transmission in countries where traffic and human movement data infrastructure is not yet developed.
Gesehen am 18.10.2022